Recent Advances in Photothermal Therapies Against Cancer and the Role of Membrane Transporter Modulators on the Efficacy of This Approach - Ahmed A. Abdulhussein Al-Ali PhD; Nameer Al Ward MSc; Mohammad A. Obeid PhD; Carsten Uhd Nielsen PhD; Paul A. Mulheran PhD; Mohammed M. Al Qaraghuli PhD (Technology in Cancer Research & Treatment, 2023)
Recently, much research is focused on the use of photothermal therapy (PTT) as an advanced method to treat various types of cancer. The PTT approach primarily utilizes nanoparticles (NPs) made from metals, carbon, or semiconductors that can convert near-infrared laser irradiation, which penetrates tissues, into local heat that induces cancer cell death. An alternative approach is to utilize NPs (such as liposomes) to carry suitable dye molecules to the same end. Numerous studies concerning PTT have shown that local heat released in cancer cells may suppress the expression of membrane transporter proteins such as P-glycoprotein (P-gp) and multidrug resistance-associated protein 1 (MRP1), thus enhancing cytotoxicity and reverse multidrug resistance. In addition, because NPs may be loaded with different substances, researchers have designed multifunctional NPs for PTT by including several agents such as membrane transporter modulators, anticancer drugs, and photothermal agents. This review will focus on the recent advances in PTT utilizing various types of NPs, and their components and characteristics. In addition, the role of membrane transporters in PTT will be highlighted and different methods of transporter modulation will be summarized from several PTT studies in which multifunctional NPs were used to treat cancers in vitro and in vivo .